1999
DOI: 10.1016/s0005-2736(99)00043-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effects of salicylate on tonic and phasic block of Na+ channels by class 1 antiarrhythmic agents in the ventricular myocytes and the guinea pig papillary muscle

Abstract: Salicylate enhanced tonic and phasic block of Na+ channels induced by class 1 highly liposoluble antiarrhythmic agents. Based on the modulated receptor hypothesis, it is probable that this enhancement was mediated by an increase in the affinity of Na+ channel blockers with high lipid solubility to the inactivated state channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The enhancing effect of salicylate on quinidineinduced block of Na + channels does not depend on the tissue-specific structures of Na + channels In a previous study we found that salicylate selectively increased the quinidine-bound inactivated Na + channels, enhancing thereby both tonic block and UDB by quinidine in guinea-pig ventricular myocytes (23). The structural differences among channel proteins may account for tissue-specific sensitivity Fig.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The enhancing effect of salicylate on quinidineinduced block of Na + channels does not depend on the tissue-specific structures of Na + channels In a previous study we found that salicylate selectively increased the quinidine-bound inactivated Na + channels, enhancing thereby both tonic block and UDB by quinidine in guinea-pig ventricular myocytes (23). The structural differences among channel proteins may account for tissue-specific sensitivity Fig.…”
Section: Discussionmentioning
confidence: 61%
“…As described previously (3,12), the voltagedependent inactivation curve of Na + channels (with quinidine) and concentration dependence of quinidine-induced tonic block were calculated for different K d values; the K dI value was determined for the state model to reproduce the experimental V h and IC 50 values, with the K dR value set equal to the experimental IC 50 at an HP of −140 mV. Rate constants for state transitions were formulated as functions of the Gibbs free energy composed of chemical and potential terms, as described in our previous articles (1,23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atrial myocytes were enzymatically isolated as described previously (17). Cells were dispersed in the recording bath and superfused with Tyrode's solution containing (in mmol/l) 140 NaCl, 5.4 KCl, 0.5 MgCl2, 1.8 CaCl2, 5 HEPES and 5.5 glucose (pH 7.4).…”
Section: Cell Isolationmentioning
confidence: 99%